CONSTRUCTION OF ISLAMIC CHARACTER EDUCATION MULTICULTURAL PERSPECTIVES AT TEBUIRENG ISLAMIC BOARDING SCHOOL JOMBANG - Maskuri; Djunaidi Ghony; Saihul Atho’ A’alul Huda (Journal Education Multicultural of Islamic Society, 2023)
The issue of character education and morality for the Indonesian generation entering the era of society 5.0 has received serious attention from all circles, both from the government and the community. This is motivated by the fact that there are a number of cases concerning morality and national character which are increasingly showing a shift and need to be improved immediately. Pesantren Tebuireng is well aware of this phenomenon. This pesantren has implemented character education for a long time, and even since the first time this institution was founded. The view that has always been used as a guide for this pesantren is al-muhafadzatu 'ala al-Qadimi al- Salih wa al-Akhdu bi al-Jadidi al-Ashlah.`The purpose of this study is to uncover, describe, analyze, and then provide an interpretation of the research findings; 1) Exploration of the Value of Multicultural Perspective Character Education 2) Practice of Multicultural Perspective Character Education and 3) Construction Model of Multicultural Perspective Character Education. The theory used in the value exploration aspect uses the Grand Theory of multiculturalism offered by Abdullah Aly. Meanwhile, in the construction and practical aspects, Peter L. Berger and Thomas Luckman, Imam al-Ghazali, James A. Banks, and Thomas Likona's theories are used. This research method is categorized as qualitative research while the approach is a case study. Data collection techniques were carried out through, a) observation, b) in-depth interviews c) document analysis. The data source was selected through a snowball pattern (snowball sampling). While the data analysis technique refers to the interactive model of Miles, Huberman, and Saldana, namely through; (1) data condensation; (2) presentation of data, and (3) drawing conclusions. Confirmability is carried out through data collection, data reconstruction. Checking the validity of the data is done through extension of participation, persistence of observation, and triangulation. The results of this study indicate that: 1) the exploration of the character values of the multicultural perspective that grows and develops in this boarding school there are 22 values which are conceptually grouped into three parts: a) the values of nationalist characters, b) values of social character, c) religious values 2) the praxis of educational learning is implemented through activities and various dimensions or approaches. 3) Thus, the findings of the new model in this study are a multiculturalist spiritual construction model and a transformative construction model: Traditional & Modern integration.